Antioxidant, Enzyme Inhibitory, and Molecular Docking Approaches to the Antidiabetic Potentials of Bioactive Compounds from Persicaria hydropiper L. (14th April 2022) - Ayaz, Muhammad; Sadiq, Abdul; Mosa, Osama F.; Zafar, Tariq Abdalla; Eisa Hamdoon, Alashary Adam; Elkhalifa, Modawy Elnour Modawy; Elawad, Mohammed Ahmed; Ahmed, Alshebli; Ullah, Farhat; Ghufran, Mehreen; Kabra, Atul
Abstract : Introduction . Natural products are among the most useful sources for the discovery of new drugs against various diseases. Keeping in view the ethnobotanical relevance ethnopharmacological significance of Polygonaceae family in diabetes, the current study was designed to isolate pure compounds from Persicaria hydropiper L. leaves and evaluate their in vitro and in silico antidiabetic potentials. Methods . Six compounds were isolated from the chloroform-ethyl acetate fractions using gravity column chromatography and were subjected to structure elucidation process. Structures were confirmed using 1 H-NMR, 13 C-NMR, and mass spectrometry techniques. Isolated phytochemicals were subjected to in vitro antidiabetic studies, including α -glucosidase, α -amylase inhibition, and DPPH, and ABTS antioxidant studies. Furthermore, the in silico binding mode of these compounds in the target enzymes was elucidated via MOE-Dock software. Results . The isolated compounds revealed concentration-dependent inhibitions against α -glucosidase enzyme. Ph-1 and Ph-2 were most potent with 81.84 and 78.79% enzyme inhibitions at 1000  µ g·mL −1, respectively. Ph-1 and Ph-2 exhibited IC50 s of 85 and 170  µ g·mL −1 correspondingly. Likewise, test compounds showed considerable α -amylase inhibitions with Ph-1 and Ph-2 being the most potent. Tested compounds exhibited considerable antioxidant potentials in both DPPH and ABTS assays. Molecular simulation studies also revealed top-ranked confirmations for the majority of the compounds in the target enzymes. Highest observed potent compound was Ph-1 with docking score of −12.4286 and formed eight hydrogen bonds and three H-pi linkages with the Asp 68, Phe 157, Phe 177, Asn 241, Glu 276, His 279, Phe 300, Glu 304, Ser 308, Pro 309, Phe 310, Asp 349, and Arg 439 residues of α -glucosidase binding packets. Asp 68, Glu 276, Asp 349, and Arg 439 formed polar bonds with the 3-ethyl-2-methylpentane moiety of the ligand. Conclusions . The isolated compounds exhibited considerable antioxidant and inhibitory potentials against vital enzymes implicated in T2DM. The docking scores of the compounds revealed that they exhibit affinity for binding with target ligands. The enzyme inhibition and antioxidant potential of the compounds might contribute to the hypoglycemic effects of the plant and need further studies.